Pengetahuan Ibu Tentang Pemanfaatan Tanaman Obat Untuk Asam Urat - Indri Kusuma Dewi; Agus Winarso; Rapim Yuanditra (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Knowledge, PKK Plants, Drugs For Gout. The purpose of this study was to determine how the PKK knowledge about the use of herbs for uric acid in the village of Klaten Danguran South. This research is quantitative descriptive study, with cross sectional approach to the subject of this study is the PKK of 50 samples. Measuring tool used is a questionnaire. The results showed that the PKK knowledge about the use of herbs for uric acid in the village of Klaten Danguran South included in the category enough by 52%, both by 38%, and 10% less category. PKK knowledge about the use of medicinal plants for acid in the village of Klaten Danguran South in the category enough.